2013
DOI: 10.1016/j.icarus.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Rotational characterization of Hayabusa II target Asteroid (162173) 1999 JU3

Abstract: The Japanese Space Agency's Hayabusa II mission is scheduled to rendezvous 2 with and return a sample from the near-Earth asteroid (162173) 1999 JU3. 3Previous visible-wavelength spectra of this object show significant variability 4 across multiple epochs which could be the result of a compositionally hetero-5 geneous surface. We present new visible and near-infrared spectra to demon-6 strate that thermally altered carbonaceous chondrites are plausible compo-7 sitional analogs, however this is a tentative asso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 43 publications
4
39
1
Order By: Relevance
“…We visually inspected the 30 best matches proposed by the tool over the several thousands of sample spectra in RELAB, to compare the asteroid and meteorite spectral features. We found that most of the best fitting meteorites are unusual/heated CM and CI carbonaceous chondrites, in agreement with Moskovitz et al (2013) and Sugita et al (2013). In particular, the best-fit spectra for our X-shooter data are represented by samples of the CM carbonaceous chondrite Murchison, heated in the laboratory to 900−1000…”
Section: Spectrasupporting
confidence: 75%
See 1 more Smart Citation
“…We visually inspected the 30 best matches proposed by the tool over the several thousands of sample spectra in RELAB, to compare the asteroid and meteorite spectral features. We found that most of the best fitting meteorites are unusual/heated CM and CI carbonaceous chondrites, in agreement with Moskovitz et al (2013) and Sugita et al (2013). In particular, the best-fit spectra for our X-shooter data are represented by samples of the CM carbonaceous chondrite Murchison, heated in the laboratory to 900−1000…”
Section: Spectrasupporting
confidence: 75%
“…A worldwide observational campaign of this body was carried out during the observational opportunity in 2012. Moskovitz et al (2013) noticed that there is no detectable rotational variation in the spectra at 0.5−0.9 µm to an accuracy of ∼4%. On the contrary, Lazzaro et al (2013) suggested that there could be differences in the UV wavelength region, showing a spectral drop-off at ∼0.4 µm by 10−30%.…”
Section: Introductionmentioning
confidence: 97%
“…However its size, rotation period, and the Sun-Earth-asteroid geometry during the mission phase, where the solar panel and antennas can face towards the Sun and Earth simultaneously, are suitable for the sample return mission in 2014-2020 (Table 1; Binzel et al, 2001;Hasegawa et al, 2008;Kawakami et al, 2010;Müller et al, 2011;Kim et al, 2013). Ground-based spectroscopic observations have confirmed that the asteroid is a C-type asteroid with a low albedo of ~0.06-0.07 (Vilas, 2008(Vilas, , 2012Abe et al, 2008;Hasegawa et al, 2008;Campins et al, 2009;Müller et al, 2011;Moskovitz et al, 2012;Sugita et al, 2012;Lazzaro et al, 2013;Pinilla-Alonso et al, 2013). A possible 0.7-µm absorption feature obtained in July 2007 by Vilas (2008) is common for CM-type chondrites and is attributed to electron transfer between ferrous and ferric iron in hydrous silicates.…”
Section: Target Asteroid 1999 Jumentioning
confidence: 99%
“…A low-resolution near-IR spectrum (Pinilla-Alonso et al 2013) confirmed the primitive nature of the C-type object Ryugu. Two independent studies on the rotational characterisation of the Hayabusa2 target asteroid (Lazzaro et al 2013;Moskovitz et al 2013) found featureless spectra with very little variation, indicating a nearly homogeneous surface. However, one key element necessary for detailed mission planning and a final radiometric analysis was still not settled: the object's spin-axis orientation.…”
Section: Introductionmentioning
confidence: 99%